The Effect of applying a Family Psycho-Education Program on Medication Adherence Behaviors among Schizophrenia Patients in a Community, Somdejprapiyamaharachrommaneeyaket Hospital, Kanchanaburi Province - Pengkred, Chatchasaa (Journal of Nursing and Public Health Research, 2021)
The objective of this quasi-experimental study was to compare medication adherence behaviors among patients with schizophrenia in a community, before and after applying the family psycho-education program. Thirty participants were recruited by purposive sampling. Participants were diagnosed with schizophrenia and were being treated in the psychiatric clinic, the outpatient department, Somdejprapiyamaharachrommaneeyaket Hospital, Kanchanaburi Province between September 17 and October 22, 2021. The research instruments were a family psycho-education program that proposed by the concept of Anderson et al. (1980) and the medication adherence questionnaire. The reliability of this questionnaire was 0.87. Data was analyzed using descriptive statistics and paired sample t-test. The results showed that after program completion, participants had significantly higher scores of medication adherence behaviors ( =4.66, SD=0.84) before enrolling the program ( = 1.53, SD= 0.13) (p-value <0.001). Our results suggested that a Family Psycho-education Program can be used to promote medication adherence behaviors among patients with schizophrenia. Nursing and other health care providers can apply this program in order to reduce recurrent hospitalization.